Awal Waktu Salat Magrib Berdasarkan Ketinggian Daerah di Kabupaten Jeneponto (Studi Perbandingan Dengan Jadwal Waktu Salat Sepanjang Masa) - Kartini, Selvira Febriani; Alimuddin; Muh. Akmal, Andi (HISABUNA: Jurnal Ilmu Falak, 2024)
The determination of prayer times is based on the phenomenon of the sun that is visible to the five senses. As for astronomy, sunset time begins when the sun sets. The setting of the sun here means that the entire "disk" of the sun has "entered" below the horizon (horizon). The lowness of this horizon is strongly influenced by the altitude. The higher the position of our eyes, the greater the lowness of the horizon. Thus, a place that is higher will see celestial bodies rise earlier and see celestial bodies set later. Along with the development of the times and science and technology, various software or prayer time schedules appeared all the time made by astronomers. This type of research uses field research or field research because it uses a qualitative approach where researchers directly observe the subjects studied in the field. The data sources used are primary data and secondary data. The primary data of this study are data obtained from observations and interviews. The secondary data in this study is a source of information that supports this research. From the results of this study it was found that: 1. The reality of the start of the evening prayer time is based on the altitude of the area in Jeneponto Regency. 2. Implementation of Prayer Time Schedules of All Time. 3. Comparison of the start of the evening prayer time based on the elevation of the area in Jeneponto Regency with the schedule of all time prayers. Meanwhile, the reality of the start of the prayer time based on the height of the place is not an influence because the standard among the community is the sound of the call to prayer at the mosque. The use of prayer time schedules is generally used in mosques, especially in the Jenepinto Regency area. Comparison of the start of the prayer time with the all-time prayer schedule, in the highlands there is a difference of 2-3 minutes and in the lowland areas there is a difference of 1-2 minutes with the schedule of all-time prayer times, while in the highlands and lowlands there is a difference of 1 minute and not a problem. The implication of this research is that determining the coordinates used as a reference is also important because differences in taking regional coordinates will cause differences in the results of schedule calculations. A good timetable calculated specifically for a city, and duly issued by the competent authority. Keywords: Prayer times, Altitude, Jeneponto Regency